👤

1/7*(4/3*(5+x-1/2)+6)=2

Răspuns :

Răspuns:

Explicație pas cu pas:

5 + ( x - 1 ) / 2 = ( 10 + x - 1 ) / 2 → paranteza rotunda pentru ( x - 1 ) / 2

____________________________________

1 / 7 × [ ( 4 / 3 ) × ( 10 + x - 1 ) / 2  + 6 ] = 2

( 4 / 3 ) × ( 10 + x - 1 ) / 2  + 6 = 2 : ( 1 / 7 ) = 2 × 7 = 14

( 4 / 3 ) × ( 10 + x - 1 ) / 2 = 14 - 6

( 4 / 3 ) × ( 10 + x - 1 ) / 2  = 8

( 10 + x - 1 ) / 2  = 8 : ( 4 / 3 ) = 8 × ( 3 / 4 ) = 6

10 + x - 1 = 2 × 6

10 + x - 1 = 12

10 + x = 12 + 1

10 + x = 13

x = 13 - 10

x = 3

_____________________________________________

Daca x NU este supra 2, atunci solutia este:

1 / 7 × [ 4 / 3 × ( 5 + x - 1 / 2 ) + 6 ] = 2

( 4 / 3 ) × ( 10 / 2 + 2 x / 2 - 1 / 2 ) + 6 = 2 : 1 / 7 = 2 × 7 = 14

( 4 / 3 ) × ( 10 / 2 + 2 x / 2 - 1 / 2 = 14 - 6 = 8

( 10 + 2 x - 1 ) / 2 = 8 : ( 4 / 3 ) = 8 × ( 3 / 4 ) = 6

10 + 2 x - 1 = 2 × 6

2 x = 12 + 1 - 10

2 x = 3

x = 3 / 2

Răspuns:

Explicație pas cu pas:

1 / 7 × [ ( 4 / 3 ) × ( 10 + x - 1 ) / 2  + 6 ] = 2

( 4 / 3 ) × ( 10 + x - 1 ) / 2  + 6 = 2 : ( 1 / 7 ) = 2 × 7 = 14

( 4 / 3 ) × ( 10 + x - 1 ) / 2 = 14 - 6

( 4 / 3 ) × ( 10 + x - 1 ) / 2  = 8

( 10 + x - 1 ) / 2  = 8 : ( 4 / 3 ) = 8 × ( 3 / 4 ) = 6

10 + x - 1 = 2 × 6

10 + x - 1 = 12

10 + x = 12 + 1

10 + x = 13

x = 13 - 10

x = 3